Proposing a smart sustainable city framework: The construction practitioners' perspective - Tan, Khai Zhi (2020)
The exponential growth of population would threaten the availability of resources globally. In other words, some significant negative impacts such as urbanization and resource depletion might be an issue faced globally. Several researches had been carried out to tackle these major issues and it was discovered that smart city concept with sustainable features is the optimal solution to overcome the crisis confronted by all the cities. Several previous studies were conducted on defining and integrating the approaches of smart city. However, there is a lack of studies focusing on the smart city's elements and components, and how it achieves sustainability. On top of that, there are also limited studies on the awareness and component of smart sustainable city in Malaysia. Therefore, this research aims to identify the components of smart sustainable city and propose a smart sustainable city framework from the perspective of construction practitioners in Malaysia. Quantitative approach method was applied as the research method. The dimensions and components of smart sustainable city were identified through review of literature. There were five (5) dimensions, seven (7) components and seventeen (17) sub-components of smart sustainable city discovered. Questionnaire were designed and distributed to four hundred (400) construction practitioners consisted of architect, engineer, main contractor and quantity surveyor. A total set of 125 surveys were collected from the respondents. Cronbach’s Alpha Reliability Test was applied to determine the reliability of the data before proceeding to further data analysis. Then, arithmetic means was conducted on the data obtained related to dimensions, components and sub-components to determine the mean ranking. The findings reveal that the respondents are aware of the human factor in achieving smart sustainable city and smart data appeared to be the most important component followed by smart energy and smart building from the view of construction practitioners. Kruskal-Wallis Test was performed as the last data analysis method to reveal significant difference across the construction practitioners on the components of smart sustainable city. A smart sustainable city framework was proposed based on the data evaluated in this research. The findings in this research could be disseminated to the Malaysian Government, professional bodies and relevant parties to increase the level of awareness of citizens towards smart sustainably city and accelerate the smart sustainable city implementation for future city.